The role of values in careers - Pope, Mark, 1952-; Flores, Lisa Y. 1969-; Rottinghaus, Patrick J. (Emerald Publishing Limited : IAP, Information Age Publishing, Inc., 2014)
Values are of critical importance in the practice of career counseling as evidenced by the pervasive use of values surveys and values card sorts by career counselors, vocational and counseling psychologists, career development facilitators, career coaches, and other career development practitioners.The purpose of this book is to provide practitioners, faculty, and researchers in vocational psychology and career counseling with a foundational tool to guide their work. This book focuses on the critical role that values play in a person's career, addressing values from a broad array of perspectives, including cultural and international perspectives, to illuminate the place of values within vocational psychology and career development.The book will be directed primarily toward psychology and counselor education faculty who teach advanced undergraduate and graduate courses in vocational psychology, career development, career assessment, and career counseling. Although there is a range of readership (undergraduate and graduate students as well as professionals already in the field), the authors understand the differences in reading level and agree to write for all levels.